Bangunan Ilmu Politik Hukum diantara Ilmu-ilmu Sosial dan Ilmu Hukum - Mustikarini, Indriyana Dwi (Universitas Merdeka Madiun, 2020)
Abstractâ€” This paper aims to describe the Building of Legal Political Science between Social Sciences and Legal Studies in Indonesia. This research focuses on the study of the legal, political science of other social sciences. The method used in this research is normative juridical. This method examines the applicable laws and regulations as well as theoretical from a variety of literature, relating to the politics of law in the formation of legislation. The results of this study indicate the relationship between law and political science that law is determined by politics, so the law is formed based on expectations or what should be (das sollen). Instead of politics determined by law, the law was formed by agreement of the political elite / actual reality (das sein). While law and politics are interdependent, the law is developed based on what should be and actual reality (das Sollen-Sein).Â Keywordsâ€”: legal politics; legal science; political science.